Enhance Witness Protection for Corruption Eradication Cases of Criminal Law Policy - Tanjung, Andry Syafrizal (Budapest International Research and Critics University, 2021)
Witness protection policies in corruption cases need to be optimized because they can be an alternative legal instrument in efforts to eradicate corruption. This shows that the protection of witnesses and victims is an important and urgent legal aspect; this is because the criminal law policy in the process of eradicating corruption places more emphasis on the perpetrators and pays less attention to the witnesses involved in legal investigations. It is necessary to optimize the role of LPSK in criminal law policies, including in providing protection for witnesses in cases of eradicating corruption, all elements of society hope that it will not become an unresolved problem. So far, criminal law policies in efforts to eradicate corruption have placed more emphasis on the perpetrators. Therefore, it is important to carry out legal reforms to the witness protection law in the process of eradicating corruption. It is necessary to optimize the role of LPSK in criminal law policies, including in providing protection for witnesses in cases of eradicating corruption; therefore, it is important to carry out legal reforms to the witness protection law in the process of eradicating corruption. It is necessary to optimize the role of LPSK in criminal law policies, including in providing protection for witnesses in cases of eradicating corruption; therefore, it is important to carry out legal reforms to the witness protection law in the process of eradicating corruption.